Penggunaan Tepung Sagu Dalam Pembuatan Rendang Telur Dan Pengaruhnya Terhadap Kualitas Kimia - Sukatno Sukatno; Irdha Mirdhayati; Dewi Febrina (State Islamic University of Sultan Syarif Kasim Riau, 2017)
Rendang telur is one of the Indonesian local foods that were popular in west Sumatra community. Rendang telur is presented in combination egg crackers and dried rendang seasoning. Generally, the main ingredient used in making egg crackers was combination of rice flour and wheat flour. This research was conducted to study the using of sago flour as a main ingredient due to sago had high availability in Riau province and utilization of non rice starch. The aims of this research was to know the chemical properties of Rendang telur that were made by using sago flour. The experimental design was Complete Randomize Design with four treatments and four replications.The treatments were amount of sago flour that were used, consists of A (rice flour 25 g as a control), B (sago flour 25 g), C (sago flour 30 g) and D (sago flour 35 g). Variable analyzed were protein content, moisture content, lipid content, acid value and content of free fatty acid. The result show that the protein content ranged between9.14-6.42% wb, the moisture content ranged between 2.94-2.04%, fat content ranged between 41.01-30.6% wb, acid value andfree fatty acid ranged between 1.70-2.14 mg and 1.09-1.37%, respectively. It can be concluded that sago flour could use asreplacer rice flour if amount added is not more than 30 g based on protein content. An addition of 35 g sago flour could reduce protein content, but non significance effect to moisture content, fat content, acid value and free fatty acid content.